PERANCANGAN VISUAL BRANDING KOTA SAWAHLUNTO - FITRI YANTI, Dra. Zubaidah, M.Sn., San Ahdi, M.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2015)
Sawahlunto is a small town located in the province of West Sumatra which has an area of 27344.7 ha. Discovered in 1868 and became a city that has the administration in 1918. Sawahlunto is the only tourism -oriented town on mining.The city is nicknamed the Black Pearl and the town cauldron because of the topography that resembles a frying pan. Sawahlunto as a tourism city does not have any visual branding. Visual branding is to create a brand to establish a positive image for the brand through sight (visual). For this reason underlyingthe visual design of this branding.Designing visual identity such as logo , tagline , and this icon was taken from the cauldron shape which is a nickname for the city Sawahlunto and adapted to the philosophies of Sawahlunto city. This design uses SWOT analysis method to find the weaknesses, strengths, opportunities, and threats Sawahlunto city as well as a differentiating factor with competitors city.Designing visual branding for Sawahlunto city is a logo, tagline, and icons that are applied to the main media billboard. Media support in the form of stickers, key chains, t-shirts, totebag, wayfinding, manual book, mug, pin, and watches.Kata Kunci : Visual branding, Sawahlunto, Logo, Billboard.